RETRACTED: Study the influence of using guide vanes blades on the performance of cross-flow wind turbine (Retracted Article) - Yahya, Waled; Kou Ziming; Wu Juan; Al-Nehari, Mohammed; Li Tengyu; Ren Qichao; Alhayani, Bilal (SPRINGER HEIDELBERG, 2021)
A cross-flow wind turbine has a high torque coefficient at a low tip speed ratio; therefore, it is a good candidate for a self-starting turbine. This study aims to investigate the best configuration between guide vanes and cross-flow vertical axis wind turbine. The experiment test was carried out to determine the turbine with the highest power coefficient. The cross-flow turbine has 14, 18, and 22 blades with using 6,10 and 14 blades of guide vane (GV) was developed in this study, employing 15 degrees, 25 degrees, 35 degrees, 45 degrees, 55 degrees, 65 degrees, and 75 degrees of tilt angles in fifth different wind speed conditions 4 m/s, 6 m/s, 7.5 m/s, 9.20 m/s, and 11 m/s. The turbine has 22 blades with 14 GV blades at 55 degrees of tilt angle blades producing more remarkable turbine performance improvement than other blades. The highest power coefficient (CP) of cross-flow using 14 GV blades at 55 degrees was 0.0162 at 0.289 TSR, which increased around 59% of the turbine's performance using GV.
Keywords: Cross-flow wind turbines; Guide vanes (GV); Tilt angles; Power coefficient (CP); SAVONIUS ROTOR; SHAPE OPTIMIZATION; IMPROVEMENT; SIMULATION; Science & Technology - Other Topics